Pengaruh Kualitas Pelayanan Administrasi Kependudukan Dan Kinerja Pegawai Terhadap Kepuasan Masyarakat - Emilia Pebrianti; Enas Enas (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Population administration plays a very important role in development, where it can be known about population data and information that is in accordance with the conditions of the population and the conditions of the area where they live. The Disdukcapil of Cilacap Regency, as the executor of population services, must provide excellent service to the community. However, in reality, KTP and KK services for the last 5 years at Disdukcapil, Cilacap Regency have not been able to reach the expected target. Besides that, the achievements in 2021 have also decreased when compared to the achievements in 2022. This indicates that the service quality of the Cilacap Regency Disdukcapil has not been optimal, so that it has not been able to meet community satisfaction. This study aims to determine 1) the effect of service quality on community satisfaction, 2) the effect of employee performance on community satisfaction, and 3) the effect of service quality and employee performance on community satisfaction in the Population and Civil Registration Office of Cilacap Regency. Because of this, this study uses quantitative data which is then interpreted to produce descriptive data. Meanwhile, data collection techniques used questionnaires, and data analysis used multiple linear regression. The research results show that service quality and employee performance have a positive effect on community satisfaction. This means that if the quality of service and employee performance is getting better, then community satisfaction will also increase, and vice versa.